Gall-inducing insects in terra firme forest and reforested areas in eastern Amazon, Pará, Brazil - Almada, Emmanuel Duarte; Fernandes, Geraldo Wilson Afonso (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2011)
For the first time, data on the occurrence and richness of gall inducing insects and their host plants in a terra firme forest in the Oriental Amazon region, Porto Trombetas, Pará, Brazil are presented. In 1981 the mining company Mineração Rio do Norte, started a restoration project with native species in areas mined for bauxite. Samples of galls were taken in the dry and the wet seasons of 2002; in 36 reforested sites (from recently planted to 21 years) and in seven primary forest sites. Three hundred and nine different morphotypes of insect galls on 255 host plant species belonging to 45 plant families were recorded. The most frequent galling taxa were Diptera of the Cecidomyiidae family (97%), followed by Coleoptera, Hymenoptera, and Lepidoptera. The host plant families most attacked by galling insects were: Fabaceae (87), Chrysobalanaceae (12), Burseraceae (18), Annonaceae (15), Clusiaceae (15), Euphorbiaceae (9), Melastomatacaeae (13), Malpighiaceae (17), Anacardiaceae (11), and Apocynaceae (7). The data indicate a high richness of gall inducing insects when compared to other vegetation types in Brazil (e.g., cerrado and Atlantic rain forest).
Keywords: Amazonia; Biodiversity; Galling insects; Mining